PENETAPAN ISBAT NIKAH CONTENTIOUS YANG SALAH SATU PIHAKNYA MENINGGAL DUNIA (STUDI KASUS DI PENGADILAN AGAMA KABUPATEN MALANG PUTUSAN HAKIM NOMOR 5457/Pdt.G/2021/PA.Kab.Mlg) - Khairunnisa Khairunnisa; Ahmad Subekti; Shofiatul Jannah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Marriage isbat is a marriage that is held again because its validity is doubtful, the goal is to obtain a marriage certificate. In general, it is not explained in detail how to apply for a contentious marriage isbat application to a deceased spouse, in practice there are similar cases that were granted by the Malang Regency Religious Court Judges, such as case number 5457/Pdt.G/2021/PA.Kab.Mlg. This study focuses on the basis of the judge's consideration in granting the case and how the views of Islamic law are. The research used is descriptive qualitative using a case study strategy, which intends to understand the phenomena experienced by the research subjects by describing them in words and language. The results showed that in granting the case, the panel of judges was guided by KHI article 7 paragraphs 2 and 3, besides that the panel of judges received testimony from witnesses de auditu. Meanwhile, the marriage isbat in Islamic law is not explained in detail, but is confirmed with Surah Al-Baqarah verse 282 which explains that every muamalah must be recorded, so that couples who are married but do not have a marriage certificate can apply for a marriage isbat.Kata kunci: Contentious Marriage Isbat, Witness De Auditu, Judge's Decision